2007
DOI: 10.1021/ja068965r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Metal Coordinating Ability of Multifunctional Carbohydrate-Containing Compounds for Alzheimer's Therapy

Abstract: Dysfunctional interactions of metal ions, especially Cu, Zn, and Fe, with the amyloid-beta (A beta) peptide are hypothesized to play an important role in the etiology of Alzheimer's disease (AD). In addition to direct effects on A beta aggregation, both Cu and Fe catalyze the generation of reactive oxygen species (ROS) in the brain further contributing to neurodegeneration. Disruption of these aberrant metal-peptide interactions via chelation therapy holds considerable promise as a therapeutic strategy to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
191
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(200 citation statements)
references
References 109 publications
8
191
1
Order By: Relevance
“…From these solution speciation diagrams, the concentrations of unchelated Cu 2þ and Zn 2þ (pM ¼ − log½M unchelated ) at a specific pH value can be calculated (pCu ¼ 9.9 and 10.2 at pH 6.6 and pH 7.4, respectively; pZn ¼ 6.1 at pH 7.4). The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…From these solution speciation diagrams, the concentrations of unchelated Cu 2þ and Zn 2þ (pM ¼ − log½M unchelated ) at a specific pH value can be calculated (pCu ¼ 9.9 and 10.2 at pH 6.6 and pH 7.4, respectively; pZn ¼ 6.1 at pH 7.4). The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37).…”
Section: Resultsmentioning
confidence: 67%
“…The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37). Thus, the affinities of L2-b for Cu 2þ and Zn 2þ at the relevant pHs [for metal-induced Aβ aggregation (2-4, 7-9)] suggest that this compound is able to chelate metal ions from soluble Aβ species, which could support the results from reactivity studies of L2-b with metal-treated Aβ species (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…[14] Orvig and co-workers have investigated salen-based ligands with glucose attached as metal-chelating agents for treating Alzheimers disease. [15] We have been interested in the supramolecular assembly of Schiff base macrocycles based on salphen. [16,17] With the notion that hydrogen bonding between monosaccharidesplexes or macrocycles, we set out to prepare new Schiff base complexes with appended glucosyl or galactosyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…48,70,90 The ability of the compounds to quench the 403 ABTS˙+ radical cation was compared to Trolox, a water-soluble analog of ±--404 tocopherol (Fig. 6) Insert Fig.7 436 …”
Section: Qh 8-h 2 Qs and 8-h 2 Qt Via The Trolox Equivalent 402mentioning
confidence: 99%